Heat-resistant austenitic cast steel and exhaust member made therefrom
By optimizing the composition and microstructure of heat-resistant austenitic cast steel, the problems of shrinkage cracking and cold cracking in cast exhaust manifolds have been solved, achieving good machinability and thermal fatigue performance, reducing the use of alloying elements, and making it suitable for components such as exhaust manifolds.
Patent Information
- Application Number
- CN202380045482.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-17
- Filing Date
- 2023-06-16
- Publication Date
- 2025-01-14
AI Technical Summary
Existing heat-resistant austenitic cast steel is prone to shrinkage cracking and cold cracking when casting exhaust manifolds, and contains a large number of expensive alloying elements, resulting in low cost performance and difficulty in machining.
Heat-resistant austenitic cast steel with a specific composition containing 0.30% to 0.50% C, 0.50% to 2.0% Si, 0.50% to 2.0% Mn, 0.10% to 0.40% S, 16.0% to 21.0% Cr, 6.0% to 12.0% Ni, 0.5% to 2.0% Nb, and less than 0.80% Cu is used to control the content of manganese sulfides and niobium carbide in the microstructure to improve castability and machinability.
It achieves resistance to shrinkage cracking and cold cracking, has good machinability and thermal fatigue performance, reduces the content of expensive alloying elements, is suitable for exhaust manifolds, and is economically superior.
Smart Images

Figure CN119317728A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a heat-resistant austenitic cast steel having excellent shrinkage cracking resistance, cold cracking resistance and machinability as well as good thermal fatigue properties and reduced content of expensive alloying elements, and an exhaust member made thereof. Background Art
[0002] Exhaust components used in internal combustion engines, such as automobile engines, are particularly Figure 1 The exhaust manifold shown in is manufactured using castings that allow a high degree of freedom in shape design because they are thin-walled and have a complex shape. Since they are exposed to high-temperature exhaust gas when the motor vehicle is running, the exhaust components should have excellent heat resistance and durability at high temperatures. Therefore, austenitic heat-resistant cast steel is mainly used as their constituent material. Various compositions have been proposed for austenitic heat-resistant cast steel.
[0003] For example, WO 2009 / 104792 proposes a heat-resistant austenitic cast steel composed of the following (by mass): 0.3% to 0.6% C, 1.1% to 2% Si, 1.5% or less Mn, 17.5% to 22.5% Cr, 8% to 13% Ni, 1.5% to 4% W+2Mo (at least one of W and Mo), 1% to 4% Nb, 0.01% to 0.3% N, 0.01% to 0.5% S, the balance being Fe and unavoidable impurities, and the heat-resistant austenitic cast steel satisfies the following formulas (1) to (4):
[0004] 0.05 ≤ (C - Nb / 8) ≤ 0.6 ... (1)
[0005] 17.5 ≤ 17.5Si - (W + 2Mo) ... (2)
[0006] 5.6Si + (W + 2Mo) ≤ 13.7 ... (3)
[0007] 0.08Si + (C - Nb / 8) + 0.015Cr + 0.011Ni + 0.03W + 0.02Mo ≤ 0.96 ...(4)
[0008] [wherein the element symbol in each formula represents its content (mass %)].
[0009] WO 2016 / 052750 proposes a heat-resistant austenitic cast steel having excellent thermal fatigue properties, the heat-resistant austenitic cast steel comprising, by mass: 0.3% to 0.6% C, 0.5% to 3% Si, 0.5% to 2% Mn, 15% to 30% Cr, 6% to 30% Ni, 0.6% to 5% Nb, 0.01% to 0.5% N and 0.01% to 0.5% S, wherein the C / N ratio is 4 to 7, the balance being Fe and unavoidable impurities, wherein the ratio A / B of the Cr-carbide formation index A to the Nb-carbide formation index B is 0.6 to 1.7, wherein A and B are represented by the following formulas (1) and (2):
[0010] A = 8.5C - Nb + 0.05Cr + 0.65Ni - 5 ... (1)
[0011] B = 7.8Nb ... (2)
[0012] [wherein the element symbol in each formula represents its content (mass %)].
[0013] Although the heat-resistant austenitic cast steels disclosed in WO 2009 / 104792 and WO 2016 / 052750 have excellent thermal fatigue life at temperatures around 1000°C or higher, they contain a large amount of expensive alloying elements, resulting in poor cost performance. In addition, due to their low ductility at room temperature, thin-walled exhaust manifolds may crack (cold cracking) during cooling after casting, which may reduce product acceptability.
[0014] JP 2011-219801 A proposes an iron (Fe)-based heat-resistant austenitic cast steel, wherein the whole is taken as 100 mass % (hereinafter simply referred to as "%"), the iron (Fe)-based heat-resistant austenitic cast steel contains 0.4% to 0.8% of carbon (C), 3.0% or less of silicon (Si), 0.5% to 2.0% of manganese (Mn), 0.05% or less of phosphorus (P), 0.03% to 0.2% of sulfur (S), 18% to 23% of chromium (Cr), 3.0% to 8.0% of nickel (Ni) and 0.05% to 0.4% of nitrogen (N), and the ratio of chromium (Cr) to carbon (C) is in the range of 22.5 ≤Cr / C ≤ 57.5. However, there is a problem in that such heat-resistant austenitic cast steel is susceptible to cracking (hereinafter also referred to as shrinkage cracking) caused by micro shrinkage cavities when cast into an exhaust manifold, which may lead to a decrease in product acceptability.
[0015] In addition, SCH12, which is an austenitic heat-resistant steel specified in JIS G 5122, is not only susceptible to shrinkage cracking but also difficult to machine compared with the materials disclosed in the above documents, making it unsuitable for exhaust manifolds that require machining during manufacturing. Summary of the invention
[0016] Purpose of the Invention
[0017] Therefore, an object of the present invention is to provide a heat-resistant austenitic cast steel and an exhaust component made thereof, particularly an exhaust manifold, which contains a small amount of expensive alloy elements, is resistant to shrinkage cracking during casting and cold cracking after casting, has good machinability after casting, and has predetermined thermal fatigue properties at around 800°C.
[0018] Solution to the problem
[0019] Therefore, the heat-resistant austenitic cast steel of the present invention comprises, by mass:
[0020] 0.30% to 0.50% C,
[0021] 0.50% to 2.0% Si,
[0022] 0.50% to 2.0% Mn,
[0023] 0.10% to 0.40% S,
[0024] 16.0% to 21.0% Cr,
[0025] 6.0% to 12.0% Ni,
[0026] 0.5% to 2.0% Nb, and
[0027] Cu below 0.80%,
[0028] The balance is Fe and inevitable impurities.
[0029] In the heat-resistant austenitic cast steel of the present invention, the Si content is preferably 0.15% to 0.37% by mass, and the Nb content is preferably 0.9% to 1.6% by mass, which not only further suppresses shrinkage cracking during casting and cold cracking after casting, but also provides a better balance between machinability and thermal fatigue performance.
[0030] In the heat-resistant austenitic cast steel of the present invention, the number of manganese sulfides having an equivalent circle diameter of 1 μm or more in any cross section is preferably 350 to 2550 pieces / mm. 2, which improves machinability while ensuring oxidation resistance.
[0031] In the heat-resistant austenitic cast steel of the present invention, the area ratio of niobium carbide in any cross section is preferably 0.5% to 11.0%, which can suppress the occurrence of shrinkage cracking and provide a heat-resistant cast steel having good high temperature strength and thermal fatigue properties.
[0032] The exhaust component of the present invention is made of the above-mentioned heat-resistant austenitic cast steel.
[0033] The exhaust component is preferably an exhaust manifold.
[0034] Effects of the Invention
[0035] The heat-resistant austenitic cast steel of the present invention is resistant to shrinkage cracking during casting and cold cracking after casting, has good workability after casting, has good thermal fatigue properties at around 800° C., and achieves low cost due to the suppression of the content of expensive alloy elements. Such a heat-resistant austenitic cast steel is suitable for exhaust components of internal combustion engines, particularly exhaust manifolds. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is a schematic front view of an exhaust manifold showing one example of exhaust components.
[0037] Figure 2A 1 is a schematic plan view showing a casting from which a test piece (test piece) for evaluating minute shrinkage voids is obtained.
[0038] Figure 2B is a schematic side view showing a casting from which a test piece for evaluating micro shrinkage pores is obtained.
[0039] Figure 3A is a schematic plan view showing a step casting of a test piece obtained for observing the microstructure.
[0040] Figure 3B is a schematic side view showing a stepped casting from which a test piece is obtained for observation of microstructure.
[0041] Figure 4A This is a photograph showing the microstructure of the heat-resistant austenitic cast steel of Example 4.
[0042] Figure 4B It shows Figure 4A Photograph of a magnified view of area A. DETAILED DESCRIPTION
[0043] [1] Heat-resistant austenitic cast steel
[0044] (A) Composition
[0045] Unless otherwise mentioned, the amounts of various elements described below are expressed on a mass basis.
[0046] (1) C (Carbon): 0.30% to 0.50%
[0047] C improves the fluidity of melt and improves castability, and after solidification, it dissolves in austenite matrix and strengthens the matrix (solid solution strengthening). It also forms thermally stable hard carbide with alloying elements such as Cr (chromium) and Nb (niobium), which is dispersed in austenite matrix and improves high temperature strength. In order to effectively play such an effect, C content should be more than 0.30%. On the other hand, too much C also causes the amount of carbide precipitated to become too much, which not only reduces ductility by embrittlement, but also deteriorates machinability, so C content should be less than 0.50%. Accordingly, the scope of C content is set to 0.30% to 0.50%. The lower limit of C content is preferably 0.35%, and more preferably 0.37%. The upper limit of C content is preferably 0.45%, and more preferably 0.44%.
[0048] (2) Si (Silicon): 0.50% to 2.0%
[0049] Si improves oxidation resistance, thereby leading to improved thermal fatigue life, so the Si content should be 0.50% or more. However, too much Si makes the austenite structure unstable and leads to deterioration of castability, so its upper limit is set at 2.0%. Accordingly, the range of Si content is set to 0.50% to 2.0%. The lower limit of Si content is preferably 0.80%, more preferably 0.90%, and most preferably 1.0%. The upper limit of Si content is preferably 1.5%, more preferably 1.2%, and most preferably 1.1%.
[0050] (3) Mn (manganese): 0.50% to 2.0%
[0051] Mn is an element that not only stabilizes the austenite structure, but also forms sulfides (MnS) with S (sulfur), which are dispersed in the austenite matrix as free-cutting particles, thereby contributing to improved machinability. In order to obtain this effect, Mn should be 0.50% or more, but when it exceeds 2.0%, oxidation resistance deteriorates. Accordingly, the range of Mn content is set to 0.50% to 2.0%. The lower limit of Mn content is preferably 0.80%, and more preferably 0.90%. The upper limit of Mn content is preferably 1.5%, more preferably 1.2%, and most preferably 1.1%.
[0052] (4) S (sulfur): 0.10% to 0.40%
[0053] S combines with Mn and Cr to form MnS (sulfide) and (Mn, Cr)S (complex sulfide) dispersed in the austenite matrix. MnS and (Mn, Cr)S can be collectively referred to as manganese sulfide. Manganese sulfide has a lubricating effect, which helps to improve the machinability of heat-resistant cast steel. In order to obtain this effect, the S content is set to more than 0.10%. However, when the S content exceeds 0.40%, the high temperature strength and ductility have a stronger tendency to decrease, and the thermal fatigue performance also has a stronger tendency to decrease due to the excessive production of manganese sulfide. Accordingly, the range of the S content is set to 0.10% to 0.40%. The lower limit of the S content is preferably 0.12%, more preferably 0.15%, and most preferably 0.16%. The upper limit of the S content is preferably 0.37%, and more preferably 0.34%.
[0054] (5) Cr (chromium): 16.0% to 21.0%
[0055] Cr is dissolved in the matrix to stabilize the austenite structure, and combined with C to form a thermally stable hard carbide (Cr carbide), which is dispersed in the austenite matrix, thereby improving the high temperature strength. Cr also combines with oxygen in the air to form a strong oxide (passivation film) on the casting surface, thereby improving the oxidation resistance at high temperatures. In order to obtain such an effect, the Cr content should be more than 16.0%. However, when the Cr content exceeds 21.0%, the amount of Cr carbides dispersed in the austenite matrix becomes too much, which promotes the propagation of cracks and actually reduces the thermal fatigue performance of heat-resistant cast steel. Accordingly, the range of the Cr content is set to 16.0% to 21.0%. The lower limit of the Cr content is preferably 16.3%, more preferably 16.6%, and most preferably 17.0%. The upper limit of the Cr content is preferably 20.0%, more preferably 19.0%, and most preferably 18.7%.
[0056] (6) Ni (nickel): 6.0% to 12.0%
[0057] Ni is dispersed in the matrix to stabilize the austenite structure (like Cr) and improve the high temperature strength and oxidation resistance of the heat-resistant cast steel. Ni also improves the casting formability of thin-walled complex-shaped exhaust components such as exhaust manifolds. In order to obtain such excellent effects, the Ni content is set to 6.0% or more. On the other hand, as the Ni content increases, the amount of Ni dissolved in the austenite matrix increases, but the solid solubility limit of C decreases and thus promotes the formation of Cr carbides, which leads to a strong tendency to reduce the thermal fatigue performance of the heat-resistant cast steel. Therefore, from the perspective of suppressing the use of expensive Ni, it is preferred to set the upper limit of the Ni content to a level that ensures the required thermal fatigue performance. The upper limit of the Ni content sufficient to ensure the necessary thermal fatigue strength at around 800°C is 12.0%. Accordingly, the range of the Ni content is set to 6.0% to 12.0%. The lower limit of the Ni content is preferably 6.2%, more preferably 6.3%, and most preferably 6.5%. The upper limit of the Ni content is preferably 10.0%, more preferably 9.0%, and most preferably 8.6%.
[0058] (7) Nb (niobium): 0.5% to 2.0%
[0059] Compared with Cr, Nb is more dominantly combined with C to form fine Nb carbides (niobium carbide), thereby suppressing the formation of excessive Cr carbides and indirectly contributing to improving the high temperature strength and thermal fatigue performance of heat-resistant cast steel. In addition, Nb carbide is a eutectic carbide with austenite, and can exist as a molten liquid until the casting is about to be completely solidified, making it resistant to tiny shrinkage holes. Therefore, Nb suppresses the occurrence of shrinkage cracking caused by shrinkage holes, which may occur when manufacturing thin-walled complex-shaped castings such as exhaust manifolds. In order to obtain this effect, the Nb content is set to 0.5% or more. On the other hand, too much Nb leads to the formation of too much Nb carbide, which actually reduces the high temperature strength and thermal fatigue performance of heat-resistant cast steel. Therefore, the upper limit of the Nb content is set to 2.0%. Accordingly, the range of the Nb content is 0.5% to 2.0%. The lower limit of the Nb content is preferably 0.9%, and more preferably 1.4%. The upper limit of the Nb content is preferably 1.8%, more preferably 1.6%, and most preferably 1.5%.
[0060] (8) Cu (copper): 0.80% or less
[0061] A small amount of Cu helps to improve the ductility of the heat-resistant cast steel, and is therefore expected to suppress cold cracking after casting. Therefore, the heat-resistant cast steel of the present invention contains Cu. However, when the Cu content exceeds 0.80%, the ductility of the heat-resistant cast steel decreases, so the upper limit of the Cu content is set to 0.80%. The upper limit of the Cu content is preferably 0.50%, more preferably 0.25%, and most preferably 0.20%. On the other hand, there is no particular restriction on the lower limit of the Cu content (but not including 0%), and can be 0.05% or 0.10%.
[0062] (9) Unavoidable impurities
[0063] The heat-resistant austenitic cast steel of the present invention inevitably contains impurities from starting materials and / or auxiliary materials (such as deoxidizers). Examples of such inevitable impurities include P (phosphorus), Al (aluminum), W (tungsten), Mo (molybdenum), etc., and the content of these inevitable impurities is preferably suppressed as much as possible. For example, P significantly reduces the toughness of the heat-resistant cast steel, so its content is preferably less than 0.06%. Al forms a slag containing Al2O3 (aluminum oxide) during the melting process, which is included as an inclusion during casting, causing casting defects. Al also combines with N (nitrogen) in the air to produce hard and brittle AlN (aluminum nitride), which is included in the product, thereby reducing the ductility and machinability of the product. Therefore, the content of Al is preferably less than 0.05%. In addition, both W and Mo form carbides with C, which not only reduces the ductility of the heat-resistant cast steel, but also dissolves in the austenite matrix to reduce the amount of Cr dissolved in the matrix, thereby reducing the oxidation resistance of the matrix, and promotes the crystallization of Cr carbides to reduce thermal fatigue performance. Accordingly, the contents of W and Mo are preferably each 0.60% or less, and more preferably 0.60% or less in total.
[0064] (B) Microstructure
[0065] Figure 4A is a photograph showing the microstructure of a cut surface of a heat-resistant austenitic cast steel of Example 4 as one embodiment of the present invention, and Figure 4B It shows Figure 4A A magnified view of area A in FIG. Figure 4A As shown, the structure of the heat-resistant austenitic cast steel of the present invention is mainly composed of a gray austenite phase (matrix) 14, white niobium carbide 15, a eutectic phase 16 of niobium carbide 15 and austenite phase 14, and dark gray manganese sulfide 17. The eutectic phase 16 is distributed in a network shape, thereby filling the gaps in the dendritic austenite phase 14.
[0066] exist Figure 4BIn order to make it clearer, the boundary between the austenite phase 14 and the eutectic phase 16 is indicated by a two-dot chain line. As described above, the eutectic phase 16 exists as a molten liquid until the final stage of solidification, and fills the small gaps in the dendritic austenite phase 14 that has completely solidified, thereby suppressing the occurrence of micro shrinkage pores.
[0067] In the heat-resistant austenitic cast steel of the present invention, the area ratio of niobium carbide 15 in any cross section is preferably 0.5% to 11.0%. When the area ratio is less than 0.5%, the effect of suppressing shrinkage cracking is insufficient. On the other hand, when the area ratio exceeds 11.0%, high temperature strength and thermal fatigue performance are reduced, and machinability is also reduced. The lower limit of the area ratio of niobium carbide 15 is more preferably 1.0%, further preferably 1.8%, further more preferably 3.5%, and most preferably 5.0%. On the other hand, the upper limit of the area ratio of niobium carbide 15 is more preferably 10.0%.
[0068] Reference Figure 4B , it can be seen that a plurality of manganese sulfide particles 17 are precipitated in the microstructure of the heat-resistant austenitic cast steel of the present invention. Among these, relatively large manganese sulfide particles 17 having an equivalent circle diameter of 1 μm or more improve machinability, but extremely fine manganese sulfide particles 71 having an equivalent circle diameter of less than 1 μm do not contribute to improving machinability. Manganese sulfide particles 71 having an equivalent circle diameter of less than 1 μm are generally present in the eutectic phase 16. It should be noted that the "equivalent circle diameter" means the diameter of a circle having an area equal to the area of each particle.
[0069] In order to improve machinability, it is better to have a large number of manganese sulfide particles 17 with an equivalent circle diameter of 1 μm or more. However, if there are too many manganese sulfide particles 17, the oxidation resistance of the heat-resistant austenitic cast steel decreases. Therefore, the number of manganese sulfide particles 17 per mm in any cross section is preferably 0.1 μm or more. 2 The number of manganese sulfide particles 17 having an equivalent circle diameter of 1 μm or more is preferably 350 to 2550. 2 The lower limit of the number of the manganese sulfide particles 17 is more preferably 600, and the upper limit thereof is more preferably 1600, and most preferably 1450.
[0070] [2] Exhaust components
[0071] The exhaust component of the present invention is made of the above-mentioned heat-resistant austenitic cast steel. Preferred examples of the exhaust component are exhaust manifolds, turbine housings, integrally cast turbine housings / exhaust manifolds, catalyst cases, integrally cast catalyst cases / exhaust manifolds, and exhaust outlets, and thin-walled complex-shaped exhaust manifolds are particularly preferred.
[0072] Figure 1 An example of an exhaust manifold is shown. The exhaust manifold 1 includes a plurality of ports 2 , a flange 3 connected to each of the ports 2 , a collection portion 4 of the ports 2 , and a flange 5 connected to the collection portion 4 .
[0073] The present invention will be described in more detail by means of the following examples, without intending to limit the present invention thereto.
[0074] Examples 1 to 7 and Comparative Examples 1 and 2
[0075] 80 kg of starting material (a mixture of steel scrap, return scrap and ferroalloy containing a predetermined amount of constituent elements) was melted in air using a high frequency induction furnace (basic lining) with a melting capacity of 100 kg / charge, taken out from a furnace at 1650°C to 1700°C, and then poured into a mold at a temperature of 1590°C to 1610°C to obtain sample materials for composition analysis of Examples 1 to 7 and Comparative Examples 1 and 2. Analysis of C (carbon) and S (sulfur) was performed using a carbon / sulfur simultaneous analyzer (CS-444, available from LECO Corporation), analysis of N (nitrogen) was performed using an oxygen / nitrogen simultaneous analyzer (TC-436, available from LECO Corporation), and analysis of other elements was performed using an optical emission spectrometer (PDA-8000, available from Shimadzu Corporation). The results are shown in Table 1.
[0076] In addition, in order to produce 1-inch Y-blocks for thermal fatigue life tests (described in JIS G 5502), Figure 2A and 2B The test piece 21 shown for evaluating micro shrinkage cavities, Figure 3A and 3B The step casting 30 shown for observing the microstructure and the cylindrical test piece (not shown) having an outer diameter of 100 mm, an inner diameter of 60 mm and a length of 60 mm for the tool life test, the melts of Examples 1 to 7 and Comparative Examples 1 and 2 were poured into the corresponding molds for each test piece under the same conditions as above.
[0077] All molds used were CO2-cured alkaline phenolic molds, and were made by adding 3 mass % of a resin (Kao Step C-840, manufactured by Kao-Quaker Company, Limited) to silica sand (Nikko silica sand α6) as an aggregate.
[0078] Table 1
[0079]
[0080] Notes: (1) Fe and inevitable impurities.
[0081] (1) Evaluation of thermal fatigue performance (thermal fatigue life test)
[0082] In order to evaluate the thermal fatigue performance, the thermal fatigue life test TMF (Thermal Fatigue Test) described below was carried out. A round bar test piece with a smooth surface having a gauge length of 25 mm and a diameter of 10 mm was cut out from each 1-inch Y-block and attached to an electro-hydraulic servo material testing machine ("Servopulser EHF-ED10TF-20L", available from Shimadzu Corporation) with a constraint rate of 1.0. Each test piece was subjected to repeated heating / cooling cycles in air, each cycle including heating for 2 minutes, maintaining the temperature for 1 minute, and cooling for 4 minutes, for a total of 7 minutes, wherein the minimum cooling temperature was 150°C, the maximum heating temperature was 800°C, and the temperature amplitude was 650°C, thereby causing thermal fatigue while mechanically constraining the elongation and contraction caused by heating and cooling.
[0083] The degree of mechanical constraint is represented by the constraint ratio η, which is defined as [(elongation of free thermal expansion - elongation under mechanical constraint) / elongation of free thermal expansion]. For example, η = 1.0 means a mechanical constraint condition in which elongation of free thermal expansion is not allowed, and η = 0.5 means, for example, a mechanical constraint condition in which only an elongation of 1 mm is allowed when the elongation of free thermal expansion without mechanical constraint is 2 mm. In Examples 1 to 7 and Comparative Examples 1 and 2, thermal fatigue life tests were performed under full constraint conditions (η = 1.0) in which the test piece was not allowed to elongate during heating or cooling.
[0084] When the heating / cooling cycle in TMF is repeated under the above-mentioned mechanical constraint conditions, the tensile load on the test piece decreases due to thermal fatigue. Therefore, in the line graph of the number of heating / cooling cycles versus the tensile load that records the change in load associated with the heating / cooling cycle in TMF, when the maximum tensile load in the second cycle (corresponding to the tensile load at the lowest temperature of the cooling process) is taken as a reference (100%), the number of heating / cooling cycles until the maximum tensile load measured in each subsequent cycle drops to 75% of this reference (maximum tensile load in the second cycle) is defined as the thermal fatigue life.
[0085] (2) Evaluation of machinability (tool life test)
[0086] Machinability was evaluated by a tool life test widely used to test machinability. Tool life was defined as the time until the wear amount of the opposite flank of the tool tip reached 0.2 mm while cutting a cylindrical test piece (not shown) with an outer diameter of 100 mm, an inner diameter of 60 mm and a length of 60 mm while attached to an NC lathe, and the machinability of the test piece was evaluated by tool life. The NC lathe used was model TAC-510×1000 manufactured by Takisawa MachineTool Co., Ltd., and the tool was a blade (insert) made of a cemented carbide substrate coated with a multilayer TiCN-Al2O3-TiOCN by CVD (KCM25B VBMT160404LF or VBMT331LF, manufactured by Kennametal Inc.). Cutting was performed under wet conditions using an emulsion-based coolant (Castrol Superedge 6754, manufactured by Castrol Industrial North America Inc.) diluted to a concentration of 10% to 12%, at a tool peripheral speed of 128 m / min, a feed of 0.12 mm / tooth, and a cutting depth of 0.3 mm.
[0087] (3) Evaluation of shrinkage crack resistance (measurement of volume ratio of micro shrinkage pores)
[0088] In view of the fact that micro shrinkage holes cause shrinkage cracks, the cross-section of the test piece 21 for evaluating micro shrinkage holes shown in Figure 2 was photographed with X-rays, and the obtained image was analyzed to determine the volume ratio of the micro shrinkage holes, and the shrinkage crack resistance was evaluated based on the volume ratio of the micro shrinkage holes.
[0089] Figure 2A and 2BA casting 20 from which a test piece 21 for evaluating micro shrinkage pores is obtained is shown. The casting 20 is equipped with: a test piece portion 21 for evaluating micro shrinkage pores in which a melt poured therein finally fills, an ingate 22 connected to the upstream side of the test piece portion 21 for evaluating micro shrinkage pores, a feeder 23 connected to the upstream side of the ingate 22, a runner 24 connected to the upstream side of the feeder 23, and a sprue (not shown) connected to the upstream side of the runner 24. The test piece portion 21 for evaluating micro shrinkage pores has a substantially flat plate shape with a width of 40 mm and a length of 100 mm in the surface direction, and has a tapered shape with a thickness of 13.2 mm at the front end and a thickness of 20 mm at the rear end in the thickness direction. The ingate 22 is 40 mm wide and 12 mm thick. The feeder 23 has a truncated cone shape with a diameter of 50 mm, tapering to a diameter of about 38.5 mm at a height of 66 mm, with a spherical bottom protruding downward by about 20 mm. The flow channel 24 is 40 mm wide and 13 mm thick.
[0090] A melt having the same composition as that of the 1-inch Y-block was poured into a sand mold for producing a casting 20, and demolded after cooling to room temperature. A test piece 21 for evaluating minute shrinkage pores was cut out from the obtained casting 20, and a shot blasting treatment was performed on it.
[0091] The cross section of the test piece 21 for evaluating micro shrinkage pores was imaged at a tube voltage of 450 kV using a CT scanner (XTH 450, manufactured by Nikon Corporation), and a CT tomographic analysis image of an approximately 1.4 mm wide area at the center of the test piece 21 for evaluating micro shrinkage pores in the thickness direction was obtained at a pitch of 0.1 mm in the thickness direction using a 3D viewer (myVGL, manufactured by VolumeGraphics Co., Ltd.). Each CT tomographic analysis image was binarized into micro shrinkage pores (dark areas) and other areas (bright areas) using image processing software (Quick Grain Padplus, manufactured by Innotech Corporation), and the area of the micro shrinkage pores (dark areas) per pitch (0.1 mm) was calculated. The volume of the micro shrinkage pores (unit: mm) was calculated by integrating them within the measurement range. 3 The volume ratio of the micro shrinkage pores was calculated by dividing the volume of the micro shrinkage pores by the measured volume of the test piece 21 for evaluating the micro shrinkage pores (75,000 mm 3) to calculate.
[0092] Table 2 shows the thermal fatigue life, tool life, and volume ratio of minute shrinkage pores in Examples 1 to 7 and Comparative Examples 1 and 2.
[0093] Table 2
[0094]
[0095] The thermal fatigue lives (TMF) of Examples 1 to 7 were 120 to 255 cycles, which were found to satisfy the standard required for an exhaust manifold at 800° C. In particular, Example 1 (220 cycles) and Example 5 (255 cycles) exhibited excellent thermal fatigue lives compared to Comparative Example 2 (195 cycles). Example 5, which corresponds to JIS alloy SCH12, exhibited a thermal fatigue life that was 1.1 times that of Comparative Example 1.
[0096] The tool life of Examples 1 to 7 was 47 to 138 minutes, which was 1.8 to 5.3 times that of Comparative Example 1, and was almost equal to or greater than 61 minutes of Comparative Example 2 (having a composition similar to that disclosed in WO2016 / 052750) having a relatively long life due to high Cr and Ni contents. In particular, the tool life of Example 6 was 138 minutes, which was 2.3 times that of Comparative Example 2.
[0097] The volume ratio of the micro shrinkage pores in Examples 1 to 7 is between 8.27 × 10 -6 Up to 740 × 10 -6 , they are all smaller than Comparative Example 1. Furthermore, even compared with Comparative Example 2 having a relatively low micro shrinkage pore volume ratio due to high Cr and Ni contents, Examples 1, 4, and 5 show even lower micro shrinkage pore volume ratios, and Examples 2, 3, 6, and 7 are slightly worse, but they are all at a level showing shrinkage crack resistance that can be used for exhaust manifolds.
[0098] From the above comparison, it was found that (a) Examples 1 to 7 were superior to Comparative Example 1 in terms of machinability (tool life) and shrinkage crack resistance (represented by the volume ratio of micro shrinkage pores), and (b) even though Examples 1 to 7 had low contents of expensive Ni and Cr, they showed equivalent or better performance than Comparative Example 2 which was expensive because it contained a Ni content as high as about 1.5 to 2.0 times that of Examples 1 to 7 and a Cr content as high as about 1.3 to 1.5 times that of Examples 1 to 7.
[0099] Therefore, the heat-resistant austenitic cast steel of the present invention satisfies the standards required for a material to be used for an exhaust manifold in terms of thermal fatigue life, has a relatively long tool life, thereby having good machinability, and has a small volume ratio of micro shrinkage pores, thereby suppressing the occurrence of micro shrinkage pores that cause shrinkage cracking. Therefore, it is not only a well-balanced material for exhaust components, especially exhaust manifolds, but also has economic superiority due to its low content of precious alloy elements.
[0100] (4) Observation of microstructure
[0101] Will be from Figure 3A and 3B A sample cut out of a 10 mm thick portion 31 of the step casting 30 shown was embedded in a resin so that the cut surface was used as an observation surface, and then mirror polished to obtain a sample for observing the microstructure. The structure of the observation sample was observed using an electron probe microanalyzer EPMA (EPMA-1720, manufactured by Shimadzu Corporation), and element mapping of C, Si, Mn, S, Cr, Ni, and Nb was performed. Under the conditions of an accelerating voltage of 15 kV, a beam current of 100 mA, a pixel number of 640 × 480, and an integration time of each pixel of 20 ms / point, the structure was observed with the minimum beam diameter in any 5 fields of view at 200 times magnification. Figure 4A and 4B A backscattered electron image (COMPO) of Example 4 is shown.
[0102] (a) Identification and quantity measurement of manganese sulfide particles
[0103] Since S is distributed in the entire manganese sulfide particles at a high concentration, manganese sulfide (MnS and (Mn, Cr)S) was identified by S mapping in the microstructure observed at a magnification of 200 times using EMPA, and a mapping image in which only manganese sulfide was colored and other areas were black was obtained. The colored area corresponding to manganese sulfide had a gradation of 1500 to 100 levels according to brightness. Using image processing software (Quick Grain Padplus, manufactured by Innotech Corporation), the mapping image was binarized into an area with a brightness of 105 or more (bright area) and an area with a brightness of 104 or less (dark area), and a color inversion image in which the bright area was colored black and the dark area was colored white was obtained. The number of black areas (corresponding to manganese sulfide) and the equivalent circle diameter of each black area were measured, and the number of black areas per mm was calculated. 2 The number of black areas with an equivalent circle diameter of 1 μm or more.
[0104] (b) Measurement of the area ratio of niobium carbide
[0105] The Nb map was superimposed on the microstructure observed at 200 times magnification using EPMA, and the area ratio measurement function of EPMA was used to measure the occupied area ratio of Nb in the observed field of view. Since almost all Nb exists as NbC, the area ratio of Nb is considered to be equal to the area ratio of NbC.
[0106] The number of manganese sulfide particles and the area ratio of niobium carbide in Examples 1 to 7 are shown in Tables 3 and 4, respectively.
[0107] Table 3-1
[0108]
[0109] Note: (1) Per unit area (1 mm 2 ) is the number of manganese sulfide particles with an equivalent circle diameter of 1 μm or more.
[0110] Table 3-2
[0111]
[0112] As is apparent from Table 3-1, the observed values per mm in Examples 1 to 7 are 2 The number of manganese sulfide particles ranged from 419 to 2525, with an average value of 472 to 1537. In addition, as is apparent from Table 3-2, the maximum equivalent circle diameter of the manganese sulfide particles observed in Examples 1 to 7 ranged from 14.0 to 17.7 μm.
[0113] Table 4
[0114]
[0115] As is apparent from Table 4, the area ratios of niobium carbide observed in Examples 1 to 7 ranged from 1.0% to 10.0%, with an average value of 1.4% to 9.2%.
[0116] Example 8
[0117] This embodiment is a case in which the heat-resistant austenitic cast steel of the present invention is used for Figure 1 The embodiment of the exhaust manifold (casting component) 1 shown in FIG. It should be noted that Figure 1 The dotted lines in represent the interior of the cast component and are not visible from the outside.
[0118] 4000 kg of the starting material (which was a mixture of steel scrap, return scrap and ferroalloy containing a predetermined amount of constituent elements) was melted in air using a high frequency induction furnace (basic lining) having a melting capacity of 4800 kg / charge, taken out from the furnace at 1700° C. to 1750° C., and then poured into a furnace having a temperature of 1590° C. to 1640° C. Figure 1 The shape of the exhaust manifold cavity is shown in the mold to obtain Figure 1 The other manufacturing conditions were the same as those in Example 1. The composition of this cast part is shown in Table 5. The composition analysis method was the same as that in Example 1.
[0119] Table 5
[0120]
[0121] Notes: (1) Fe and inevitable impurities.
[0122] In the cast component produced in Example 8, cold cracking that is likely to occur particularly in thin-walled portions and shrinkage cracking that is likely to occur during casting were not observed.
[0123] Industrial Applicability
[0124] The heat-resistant austenitic cast steel of the present invention is particularly suitable for exhaust manifolds of internal combustion engines, but can also be used for other exhaust components, such as turbine housings, integrally cast turbine housings / exhaust manifolds, catalyst housings, integrally cast catalyst housings / exhaust manifolds, exhaust outlets, etc. In addition, it is not limited thereto, and can also be used for exhaust components joined to sheet metal or tubular components made of other materials. Of course, the use of the heat-resistant austenitic cast steel of the present invention is not limited to these exhaust components.
[0125] Description of Reference Numerals
[0126] 1: Exhaust manifold
[0127] 20: Obtaining castings of test pieces for evaluation of micro shrinkage cavities
[0128] 21: Test piece for evaluating tiny shrinkage holes
[0129] 22: Ingate
[0130] 23: Feeder
[0131] 24: Runner
[0132] 30: Stepped casting
[0133] 31: 10mm thick part
[0134] 14: Austenite phase
[0135] 15: Niobium carbide
[0136] 16: Eutectic phase
[0137] 17: Manganese sulfide particles
[0138] 71: Fine manganese sulfide particles
Claims
1. A heat-resistant austenitic cast steel, comprising by mass: 0.30% to 0.50% C, 0.50% to 2.0% Si, 0.50% to 2.0% Mn, 0.10% to 0.40% S, 16.0% to 21.0% Cr, 6.0% to 12.0% Ni, 0.5% to 2.0% Nb, and Cu below 0.80%, The balance is Fe and inevitable impurities.
2. The heat-resistant austenitic cast steel according to claim 1, wherein the Si content is 0.15 to 0.37% by mass, and the Nb content is 0.9 to 1.6% by mass.
3. The heat-resistant austenitic cast steel according to claim 1 or 2, wherein the number of sulfides having an equivalent circle diameter of 1 μm or more in any cross section is 350 to 2550 pieces / mm 2 .
4. The heat-resistant austenitic cast steel according to claim 1 or 2, wherein the area ratio of niobium carbide in any cross section is 0.5% to 11.0%.
5. An exhaust component made of the heat-resistant austenitic cast steel according to any one of claims 1 to 4.
6. The exhaust component of claim 5, the exhaust component being an exhaust manifold.
Citation Information
Patent Citations
Austenitic heat-resistant cast steel
JP2011219801A
Austenitic heat-resistant cast steel and exhaust system components made therefrom
WO2009104792A1
Austenitic heat-resistant cast steel having excellent thermal fatigue characteristics, and exhaust system component comprising same
WO2016052750A1